2016
DOI: 10.1111/jzs.12158
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomic composition and ploidy level among European water frogs (Anura: Ranidae:Pelophylax) in eastern Hungary

Abstract: The western Palaearctic water frogs in the genus Pelophylax comprise several distinct species and three hybridogenetic hybrid forms. In this study, we focus on the Pelophylax esculentus complex, which consists of two sexual species, Pelophylax ridibundus and Pelophylax lessonae, and their hybridogenetic hybrid, Pelophylax esculentus. Specifically, we investigated taxonomic composition and ploidy level of water frogs sampled in three different types of wetland habitats in the Hortob agy National Park (HNP), eas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 43 publications
0
12
1
1
Order By: Relevance
“…In addition, the intronic markers used could yield biased phylogenetic signals due to specific features, like retrotransposons 17 . Given the complex evolutionary history of Western Palearctic water frogs, involving frequent events of hybridization between species 19 , 20 , robust nuclear phylogenies and admixture analyses will require high-throughput genomic data.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the intronic markers used could yield biased phylogenetic signals due to specific features, like retrotransposons 17 . Given the complex evolutionary history of Western Palearctic water frogs, involving frequent events of hybridization between species 19 , 20 , robust nuclear phylogenies and admixture analyses will require high-throughput genomic data.…”
Section: Introductionmentioning
confidence: 99%
“…Symbols are the same as in fig. 1. 1995; Rybacki and Berger, 2001;Borkin et al, 2002;Borkin et al, 2004;Mikulíček et al, 2015;Herczeg et al, 2017). Regardless of the differences in taxa contribution, at all three sites we found significant male-biased asymmetry in the hybrid sex ratio (table 1).…”
Section: Genome Composition and Hybrid Sex Ratio Within Population Typesmentioning
confidence: 52%
“…An intriguing population is the L-E-R type, very rare in western Europe, where all members of the P. esculentus complex exist together. Although the L-E-R type is widely distributed in eastern Europe (Lada, Borkin and Vinogradov, 1995;Borkin et al, 2002) and was occasionally found in central Europe (Mikulíček et al, 2015;Herczeg et al, 2017), little is known about how hybrids are perpetuated in these populations.…”
Section: Introductionmentioning
confidence: 99%
“…A három zöldbékafaj lokális populációs rendszereinek pontos viszonyait célzott, nagy mintaszámú és lefedettségű genetikai vizsgálatokkal lehet csak megállapítani a fajkomplexumra jellemző összetett hibridizációs mechanizmusok miatt (Vitt & Caldwell 2014). Herczeg et al (2016) vizsgálatai alapján az Egyek-pusztakócsi mocsárrendszerre a kis tavibéka és kecskebéka által alkotott "LE" típusú populációs rendszer lehet jellemző, amely egybeesik saját megfigyeléseinkkel. A vizuális módszerekkel (nappali és esti vizuális keresés és kézi hálózás) minden faj esetében találtunk egyedeket.…”
Section: éRtékelésunclassified